The Impact of the Roman Army (200 B.C. - A.D. 476) Economic, Social, Political, Religious and Cultural Aspects - de Blois, Lukas; Lo Cascio, Elio (Brill, 2007)
This sixth volume of the network Impact of Empire offers a comprehensive reading on the economic, political, religious and cultural impact of Roman military forces on the regions that were dominated by the Roman Empire.